The impact of social media on mental health: A psychological study of anxiety, depression, and self-esteem - Nur Ummi Fatayati (C-DISC, 2025)
The increasingly intensive use of social media in everyday life has raised various concerns about its impact on mental health, particularly in relation to anxiety, depression, and self-esteem. This study aims to comprehensively examine the relationship between social media use and these three aspects of mental health through a systematic literature review (SLR) approach. Data was obtained from scientific articles published between 2018 and 2025 with the following inclusion criteria: discussing the relationship between social media use and anxiety, depression, or self-esteem; using a psychological approach; and published in indexed journals. Qualitative thematic analysis was conducted to identify patterns of relationships and psychological mechanisms that emerged from various findings. The results of the study show that intensive social media use is associated with increased anxiety and depression and decreased self-esteem. The main psychological mechanism found is upward social comparison, which is the tendency for individuals to compare themselves with the ideal standards displayed on social media, thereby triggering negative self-evaluation. Decreased self-esteem was found to be an important mediator linking social media use to the emergence of symptoms of depression and anxiety. This study confirms that uncontrolled social media use has the potential to worsen mental health, especially among adolescents and young adults. These findings have important implications for psychological interventions, digital literacy, and policies for healthier social media use.